Tissue microarrays for testing basal biomarkers in familial breast cancer cases - Rozany Mucha Dufloth; Matos, Irina; Schmitt, Fernando; Zeferino, Luiz Carlos (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: The proteins p63, p-cadherin and CK5 are consistently expressed by the basal and myoepithelial cells of the breast, although their expression in sporadic and familial breast cancer cases has yet to be fully defi ned. The aim here was to study the basal immunoprofi le of a breast cancer case series using tissue microarray technology. DESIGN AND SETTING: This was a cross-sectional study at Universidade Estadual de Campinas, Brazil, and the Institute of Pathology and Molecular Immunology, Porto, Portugal. METHODS: Immunohistochemistry using the antibodies p63, CK5 and p-cadherin, and also estrogen receptor (ER) and Human Epidermal Receptor Growth Factor 2 (HER2), was performed on 168 samples from a breast cancer case series. The criteria for identifying women at high risk were based on those of the Breast Cancer Linkage Consortium. RESULTS: Familial tumors were more frequently positive for the p-cadherin (p = 0.0004), p63 (p < 0.0001) and CK5 (p < 0.0001) than was sporadic cancer. Moreover, familial tumors had coexpression of the basal biomarkers CK5+/ p63+, grouped two by two (OR = 34.34), while absence of coexpression (OR = 0.13) was associated with the sporadic cancer phenotype. CONCLUSION: Familial breast cancer was found to be associated with basal biomarkers, using tissue microarray technology. Therefore, characterization of the familial breast cancer phenotype will improve the understanding of breast carcinogenesis.